KARAKTERISTIK HIDRODINAMIK DESAIN LAMBUNG KAPAL DENGAN RISE OF FLOOR DAN TANPA RISE OF FLOOR PADA PERAIRAN DALAM DAN DANGKAL - Bambang Sudjasta; Wiwin Sulistyawati (Bina Teknika, 2017)
In principle Manoeuvrability vessel is strongly influenced by the design of the hull, propulsion system and steering system. Some of these elements are directly give a significant effect on the hydrodynamic force and moment when the ship maneuver. Analysis of hydrodynamic aspects is a stage that is absolutely necessary in the design process of a ship, especially for ships operating in waters with varying depths. By the time the ship through the shallow waters can increase frictional resistance surge barriers and the vessel which resulted in a decrease in speed boats. The hull form with rise of floor and without the rise of floor by focusing on the analysis of the obstacles, the character of the ship motion and acceleration criteria in deep and shallow water conditions. In numerical calculations for shallow water conditions (shallow water) with a ratio of water depth and draft of the ships, h / d = 1.2 and deep water (deep water) with h / d = 20. Evaluation of the obstacles, the character motion and acceleration for heave, roll, pitch and yaw is done by combining numerical methods through Hullspeed and AQWA Ansys program. From this numerical calculation, it can be analyzed with the rise of the hull form floor and without a rise of floor optimum for deepwater and shallow.